The Gibraltar crusade castile and the battle for the strait - O'Callaghan, Joseph F. (The Middle Ages series, 2011)
Joseph O'Callaghan offers the first full and authoritative history of the epic battle for control of the Strait of Gibraltar waged by Castile, Morocco, and Granada in the late thirteenth and early fourteenth centuries-a major, but often overlooked chapter in the Christian reconquest of Spain